Tinjauan Kriminologi Tentang Korupsi dalam Penyaluran Bantuan Sosial Covid-19 di Indonesia - Fatimah Cahya Amani; Saskia Salsabila Japono; Nadira Umar Bajaber; Jasmine Fatiha Jamaila; Adzra Ardelia Tuasalamony; Raisya Syafira Zahra; Mulyadi (VISA: Journal of Vision and Ideas, 2024)
Abstract This article contains a criminological analysis of corruption in the distribution of COVID-19 social assistance in Indonesia, as a response to the economic impact of the global pandemic. Despite the government providing aid to affected communities, reports and suspicions of power abuse and corruption have arisen. To address this issue, criminological analysis is deemed important in identifying the factors influencing corruption in social assistance distribution. With this approach, it is hoped that more effective policies for preventing and addressing corruption can be formulated. This research is supported by literature studies and secondary data to provide an in-depth criminological analysis of corruption cases in the distribution of COVID-19 social assistance in Indonesia. Keyword : Criminology, Corruption, Social assistance.